Critical Failure Factors For Erp Implementation A Case Study Of Tehran Regional Electric Company, A Governmental Organization In Iran - Minoocher, Parisa; Karuppayah, Nitiabalan; Subramaniam, Prabakher (2014)
Many companies in developing countries have implemented Enterprise Resource Planning (ERP), to achieve its benefits, but still there is a lack in examining Critical Failure Factors (CFFs) that influence failure of ERP implementation in an organization. Most of previous researches and studies projects have been tried in identifying ERP Critical Success Factors (CSFs) rather than Critical Failure Factors (CFFs). It should be noted that Iran is one of the developing countries that had several of its ERP implementation projects headed to failure.